Caring for people who take care: What is already done?. Issue 5 (October 2022) - Oliveira, Carolina; Fonseca, Gabriela; Areia, Neide P.; Sotero, Luciana; Relvas, Ana Paula
Abstract: Objective: The growing prevalence and impact of cancer on the family system calls for a palliative care approach with the family as the unit of care. This study aimed at providing an overview of the intervention programs that have been developed to offer support to the family caregivers of oncologic patients receiving palliative care. Method: Sixteen articles were included in the final review, encompassing (i) studies focused on intervention programs with family caregivers of cancer patients in palliative care, (ii) studies including a pre- and post-test evaluation of the intervention program, (iii) and studies whose cancer patients were at least 18 years old. Results: A great heterogeneity was verified with respect to care settings, number of sessions, outcome measures, or timing of assessment within the reviewed programs. These findings mirrored the complexity of the palliative care approach, which is difficult to standardize. Nonetheless, some interventions with different features accomplished good and sometimes similar results. The studies' main outcomes were clustered in five categories: psychological symptomatology, general quality of life, caregiving role, family relational variables, and bereavement/grief. Moreover, 44% of the main outcomes were psychological symptomatology of family caregivers, with an emphasis toward anxiety and depression. Also shown was a growing emergence of technology use among these interventions. Significance of results: Results revealed a scarcity of family-oriented programs and lack of certified mental health professionals as interventionists. Future studies and interventions should focus on the positive outcomes of the caregiving experience and must acknowledge the cultural differences when trying to replicate programs. Considering that there is no precise formula for dealing with terminal illness and grief, we submit that family-centered and systemic lenses are excellent approaches for support during this adjustment process. In conclusion, the present study advocates for increased investment in the field, underscoring the importance of family caregivers' mental health.